1943
DOI: 10.1177/00220345430220010501
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Induced Caries in Rats

Abstract: The post-eruptive increase of fluorine in dentin and enamel has been observed in rats (1, 2) and in an adult dog (3). Fluorine has been found deposited posteruptively by the rat in molar enamel but not in dentin (4). In vitro experiments show powdered enamel and dentin (5, 6), as well as bone tissue (7) to have the property, in common with pure mineral phosphates (8,9,10), of adsorbing fluoride.The above in vivo experiments (1, 2, 3) are interesting from several aspects. First: They indicate that dentin and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1943
1943
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…demonstrated that rats fed casein plus fluorine had from 60 to 70 percent less caries than groups fed powdered milk and plain casein. These data show that resistance to caries is inherent in the rat, presumably in the enamel.McClure(44), in 1941, observed that the caries resistance of rats is correlated with the amount of fluorine in the diet; also that the fluorine content of the molar teeth of the experimental rats is changed in direct proportion to the amount of fluorine in the diet. It is of interest to note that commercial casein was found to contain 0.2 percent of fluorine (42).Cox et al(43) observed that diets containing up to 40 p. p. m. of sodium fluoride fed to pregnant rats significantly reduced the incidence of dental caries in their offspring, when compared with controllitters.…”
mentioning
confidence: 99%
“…demonstrated that rats fed casein plus fluorine had from 60 to 70 percent less caries than groups fed powdered milk and plain casein. These data show that resistance to caries is inherent in the rat, presumably in the enamel.McClure(44), in 1941, observed that the caries resistance of rats is correlated with the amount of fluorine in the diet; also that the fluorine content of the molar teeth of the experimental rats is changed in direct proportion to the amount of fluorine in the diet. It is of interest to note that commercial casein was found to contain 0.2 percent of fluorine (42).Cox et al(43) observed that diets containing up to 40 p. p. m. of sodium fluoride fed to pregnant rats significantly reduced the incidence of dental caries in their offspring, when compared with controllitters.…”
mentioning
confidence: 99%
“…Ferric chloride added to drinking water (250 ppm) was observed to reduce the prevalence of dental caries; in con trast, ferric citrate was without effect, suggesting a role for anion in the cariostatic effect of iron [McClure, 1948]. In a series of experiments, Emilson and Krasse [1972] demon strated the cariostatic effect of ferric chloride and ferrous sulfate when added to diet and drinking water.…”
Section: Discussionmentioning
confidence: 99%